Closed mitral valvotomy in pregnancy - Vosloo, S M (Division of Cardiology, 2017)
Heart disease remains the most important non-obstetric cause of maternal mortality and morbidity during pregnancy, despite its low incidence of less than 1%. This is due to the decline in the number of deaths from haemorrhage, infection and toxemia. In addition, a striking change in the pattern of proportional distribution of organic heart disease in pregnant women is being noted, with a decrease in chronic rheumatic lesions and an increase in congenital cardiac disease. In the Third World rheumatic mitral valve disease remains a most important condition during pregnancy. It is currently rarely seen in Europe and the United States. Mitral stenosis is the most commonly encountered rheumatic heart lesion that complicates pregnancy. The normal circulatory changes during pregnancy aggravate this lesion as the reduced, fixed valve area obstructs blood flow from the left atrium to the left ventricle, causing pulmonary congestion and oedema. Careful and regular follow up of these patients is essential, and surgery is indicated if optimal medical management fails. Cardiac surgery duting pregnancy represents a risk to both the foetus and the mother. For most procedures extracorporeal circulation and heparinization are necessary and adds to the · adverse effects of the operation. Closed mitral valvotomy, however, is an excellent low risk operative procedure in patients with tight mitral stenosis without causing undue harm to the foetus. Cuttler described the first attempted surgery of the mitral valve in 1923 and since then the procedure has been improved to benefit many patients with tight mitral stenosis. The first reports of closed mitral valvotomy during pregnancy were in 1952. Al though a more precise valvotomy can be obtained with an open procedure, the closed operation avoids the risks of extracorporeal circulation, particularly detrimental to the foetus. This report is a review of the Groote Schuur Hospital experience of patients with mitral stenosis requiring closed mitral valvotomy during pregnancy since 1965. The aims of the study are to analyse the outcome of the pregnancy, the effects of valvotomy during pregnancy on both the mother and the foetus, and the outcome regarding restenosis of the mitral valve.